(untitled) (Contemporary Journal of Social Science Review, 2025)
Code-switching and code-mixing continue to be a regular occurrence in the linguistic communities where English is one of the several languages they share. This paper discusses these linguistic dynamics in the World Englishes theoretical perspective coupled with analyzing their societal effects on communicative systems as well as identities formation and linguistic advances. The study explains the reasons behind code-mixing and code-switching by the speakers through evaluations of pragmatic needs and cognitive processing along with socio-cultural influences. Such practices are examined in different forms of English like Indian English, Nigerian English and Singlish to show how they shape the development of particular linguistic identity. The present paper focuses on the role of code-switching and code-mixing in language policy, but also on how it influences the educational system and the status of the English language on the international scale. This is because this study assesses the dynamics of the English language which is changing by carrying out experimental research as well as arranging the study into theoretical structures so as to enhance our understanding regarding linguistic developments within a multilingual setting.